Pretrial Detention and Incarceration Decisions for Foreign Nationals: a Mixed-Methods Approach - Wermink, Hilde (European journal on criminal policy and research, 2022)
An increase in the mobility of persons across national borders coincides with an overrepresentation of foreign nationals in the penal systems of Western Europe, though this phenomenon is not yet well understood. This paper positions itself at the intersection of migration and criminology by examining citizenship disparities in pretrial detention and whether said disparities affect incarceration outcomes. Leveraging a mixed-methods strategy, we make use of individual-level criminal case and interview data from the Netherlands. Our quasi-experimental quantitative analyses show significant and substantive differences in the assignment of pretrial detention to foreign citizens, which affects the risk of future incarceration. Our interviews reveal that citizenship disparities manifest themselves through multiple mechanisms: (i) foreign defendants are viewed as flight risks, (ii) fewer non-prison sanctions are assigned in cases involving foreign defendants, and (iii) pretrial detention is seen as an efficient method for punishment.